Oceanographic Data of the 46th Japanese Antarctic Research Expedition from December 2004 to March 2005 - オガタ, ジュン; スズキ, カズノリ; Ogata, Jun; Suzuki, Kazunori (National Institute of Polar Research, 2006)
P(論文) departmental bulletin paper